10(z+1)-5(z-2)=2(z-2)+2(z-1)

Simple and best practice solution for 10(z+1)-5(z-2)=2(z-2)+2(z-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(z+1)-5(z-2)=2(z-2)+2(z-1) equation:



10(z+1)-5(z-2)=2(z-2)+2(z-1)
We move all terms to the left:
10(z+1)-5(z-2)-(2(z-2)+2(z-1))=0
We multiply parentheses
10z-5z-(2(z-2)+2(z-1))+10+10=0
We calculate terms in parentheses: -(2(z-2)+2(z-1)), so:
2(z-2)+2(z-1)
We multiply parentheses
2z+2z-4-2
We add all the numbers together, and all the variables
4z-6
Back to the equation:
-(4z-6)
We add all the numbers together, and all the variables
5z-(4z-6)+20=0
We get rid of parentheses
5z-4z+6+20=0
We add all the numbers together, and all the variables
z+26=0
We move all terms containing z to the left, all other terms to the right
z=-26

You can always share this solution

See similar equations:

| (4a-1)=-23- | | 2(m-1)=-5(4m-m) | | -6w-14=8(w-7) | | 3(2x-3)-3=3(x-2)+9 | | X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) | | x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v | | 5x+3+15x+7=180 | | 4x+5=17;3 | | 8/x^2-1-4/x-1=2/x+1 | | 23=3/1b–2+3/4b | | (4x-25)(2x-1)=180 | | 8y+–11y+8=17 |

Equations solver categories